Häusliche Gewalt in Japan - Okaue, Masami (Zeitschrift für Japanisches Recht, 2006)
The article, which is based on a speech held by the author in Hamburg in September 2005, examines the situation regarding domestic violence in Japan. According to the author, domestic violence was not recognized as a problem in Japanese society for a long time due to traditional values and morals. Only recently has awareness of this problem risen, and laws protecting victims of domestic violence have been passed. The article deals mainly with the Law on the Prevention of Violence between Spouses and on the Protection of Victims. Under this new law, courts can issue an order preventing the violent spouse from harassing and pestering the victim or directing him to leave the home. When the law first entered into force, it met with heavy criticism for offering only inadequate protection to victims. In 2004, therefore, the law was amended. It now aims not only at protecting victims from bodily harm and threats to their life, but also at enabling victims to become independent. Further improvements are that the legal definition of violence now also comprises mental and emotional violence, not only physical violence. Furthermore, court orders may also be issued against divorced partners. Also, courts may issue orders preventing the violating spouse from harassing and pestering the couple’s children. The author appraises the law as a first and important step in combating domestic violence, but also points out the need for further improvement.